Regorafenib Promotes Antitumor Immunity via Inhibiting PD-L1 and IDO1 Expression in Melanoma - Wu, Rui-Yan; Kong, Peng-Fei; Xia, Liang-Ping; Huang, Yun; Li, Zhi-Ling; Tang, Yun-Yun; Chen, Yu-Hong; Li, Xuan; Senthilkumar, Ravichandran; Zhang, Hai-Liang; Sun, Ting; Xu, Xue-Lian; et al. (Clinical cancer research, 2019)
Immune checkpoint blockade (ICB) therapy induces durable tumor regressions in a minority of patients with cancer. In this study, we aimed to identify kinase inhibitors that were capable of increasing the antimelanoma immunity. Flow cytometry-based screening was performed to identify kinase inhibitors that can block the IFNγ-induced PD-L1 expression in melanoma cells. The pharmacologic activities of regorafenib alone or in combination with immunotherapy and were determined. The mechanisms of regorafenib were explored and analyzed in melanoma patients treated with or without anti-PD-1 using The Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) datasets. Through screening of a kinase inhibitor library, we found approximately 20 agents that caused more than half reduction of cell surface PD-L1 level, and regorafenib was one of the most potent agents. Furthermore, our results showed that regorafenib, and , strongly promoted the antitumor efficacy when combined with IFNγ or ICB. By targeting the RET-Src axis, regorafenib potently inhibited JAK1/2-STAT1 and MAPK signaling and subsequently attenuated the IFNγ-induced PD-L1 and IDO1 expression without affecting MHC-I expression much. Moreover, RET and Src co-high expression was an independent unfavorable prognosis factor in melanoma patients with or without ICB through inhibiting the antitumor immune response. Our data unveiled a new mechanism of alleviating IFNγ-induced PD-L1 and IDO1 expression and provided a rationale to explore a novel combination of ICB with regorafenib clinically, especially in melanoma with RET/Src axis activation.